Break-induced replication: unraveling each step. Issue 7 (July 2022) - Liu, Liping; Malkova, Anna
Abstract : Break-induced replication (BIR) repairs one-ended double-strand DNA breaks through invasion into a homologous template followed by DNA synthesis. Different from S-phase replication, BIR copies the template DNA in a migrating displacement loop (D-loop) and results in conservative inheritance of newly synthesized DNA. This unusual mode of DNA synthesis makes BIR a source of various genetic instabilities like those associated with cancer in humans. This review focuses on recent progress in delineating the mechanism of Rad51-dependent BIR in budding yeast. In addition, we discuss new data that describe changes in BIR efficiency and fidelity on encountering replication obstacles as well as the implications of these findings for BIR-dependent processes such as telomere maintenance and the repair of collapsed replication forks. Highlights: Break-induced replication (BIR) is driven by a migrating bubble with conservative inheritance of newly synthesized DNA and is approximately six times slower than S-phase replication. The choice between the BIR and synthesis-dependent strand annealing (SDSA) pathways of double-strand break repair is made after the initiation of repair DNA synthesis and depends on the annealing function of Rad52. Leading-strand BIR synthesis can initiate and proceed without lagging-strand synthesis, but the lagging strand is required for extensive leading-strand synthesis, likely for its protection. BIR is a pathway driving alternative telomere lengthening; however, BIR frequently interrupts while copying interstitial telomere repeats in the absence or presence of telomerase. BIR has been implicated in the recovery of replication forks collapsed following conflict with transcription; however, initiation of BIR is suppressed in the vicinity of active transcription although established BIR has no problem in traversing transcription units.